JP Transport Sdn. Bhd. haulage service study / Aishah Mohamad…[et al.] - Mohamad, Aishah; Abdullah Effendi, Azura; Baharuddin, Fatim Hamimi; Arshad, Rashidah; Mohd. Shukor, Shamsul Azren (1999)
This study is aimed at analyzing the efficiency and effectiveness of the haulage services provided by Johor Port Transport (JPT) Sdn Bhd. within the free zone are of Johor Port by looking at two perspectives; JPT customers level of satisfaction/ dissatisfaction and JPT's perception of its capacity and capabilities to satisfy its customers/ to efficiently and effectively service its customers.